Estradiol Levels Are Altered in Human Immunodeficiency Virus–Infected Pregnant Women Randomized to Efavirenz-Versus Lopinavir/Ritonavir-Based Antiretroviral Therapy. (10th November 2017) - McDonald, Chloe R; Conroy, Andrea L; Gamble, Joel L; Papp, Eszter; Hawkes, Michael; Olwoch, Peter; Natureeba, Paul; Kamya, Moses; Silverman, Michael; Cohan, Deborah; Koss, Catherine A; Dorsey, Grant; et al.
Abstract : This study found that combination antiretroviral therapy (cART) regimens differentially affect estradiol levels in pregnancy. Exposure to lopinavir/ritonavir was associated with an increase in estradiol, while exposure to efavirenz was associated with a decrease in estradiol, relative to cART-naive HIV-infected women. Abstract: Background: Combination antiretroviral therapy (cART) use in pregnancy has been associated with hormonal dysregulation. We performed a secondary retrospective analysis of longitudinal progesterone and estradiol levels in pregnancy using specimens from the Protease Inhibitors to Reduce Malaria Morbidity in HIV-infected Pregnant Women study, which randomized Ugandan human immunodeficiency virus (HIV)–infected ART-naive women to initiate either lopinavir/ritonavir (LPV/r)–based or efavirenz (EFV)–based cART. Methods: Three hundred twenty-six women (160 randomized to the EFV arm and 166 women to the LPV/r arm) with at least 1 plasma sample collected during pregnancy were included. Enrollment samples collected prior to cART initiation were used as a cART-naive comparator group. Hormone levels were quantified by enzyme-linked immunosorbent assay. Results: Estradiol levels were differentially affected by the 2 cART regimens. Exposure to LPV/r was associated with an increase in estradiol ( P < .0001), whereas exposure to EFV was associated with a decrease in estradiol ( P < .0001), relative to the cART-naive gestationally matched comparator group. Lower estradiol levels correlated with small for gestational age (SGA) ( P = .0019) and low birth weight ( P = .019) in the EFV arm, while higher estradiol levels correlated with SGA in the LPV/r arm ( P = .027). Although progesterone levels were similar between treatment arms, we observed an association between SGA and lower progesterone in the LPV/r arm ( P = .04). No association was observed between hormone levels and preterm birth in either arm. Levels of progesterone and estradiol were lower in cases of stillbirth, and levels of both hormones declined immediately prior to stillbirth in 5 of 8 cases. Conclusions: Combination ART regimens differentially affect estradiol levels in pregnancy, a hormone critical to the maintenance of a healthy pregnancy. Identifying cART regimens that minimize perinatal HIV transmission without contributing to hormonal dysregulation represents an urgent public health priority. Clinical Trials Registration: NCT00993031.